THE CONTROL REGIMES FROM PARAGUAYAN TERRITORY (1870-2019) - Pereira, Lorena Iza; Fernandes, Bernardo Mancano [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2021)
The starting point of this article is the critique of homogenization of land grabbing process, addressed herein as territorial control. Assuming that control over territory is the result of interaction of general (global), particular (regional) and singular (national) dynamics, we argue for the existence of regimes of control over territory in time and space. Through the research conducted in Paraguay, we have identified three regimes in the historical period 1870 to 2019: I) 1870-1950; II) 1950-1990 and III) 1990-today, each of which is characterized by unique processes, strategies, impacts and resistances. Thus, the objective is to debate on the control of Paraguayan territory from 1870 to 2019, highlighting the different global, regional and national dynamics which have shaped this control at different points in history. By means of quantitative and qualitative methodologies, we concluded that historically Paraguay has behaved like a territory designed for the expansion needs of the regional capital. Under the first regime to officials from Argentina required to incorporate territories in order to the Quebracho exploitation, already in the second system, Brazilians were in need of expanding their agricultural frontier due to Green Revolution, and at present, Brazilian, Argentine and Uruguayan agents control an important part of Paraguay's territory promoting a development model guided by the commodity consensus. Despite all the peculiarities and singularities, what drives the control of the territory at all times is the need to ensure, at all costs, the accumulation of capital.
Keywords: Foreignization of land; Agrarian issue; Territory; South America